Application of loaded graphene oxide biomaterials in the repair and treatment of bone defects: a review - Jinyi Xing; Shuzhong Liu (Bone & Joint Research)
Addressing bone defects is a complex medical challenge that involves dealing with various skeletal conditions, including fractures, osteoporosis (OP), bone tumours, and bone infection defects. Despite the availability of multiple conventional treatments for these skeletal conditions, numerous limitations and unresolved issues persist. As a solution, advancements in biomedical materials have recently resulted in novel therapeutic concepts. As an emerging biomaterial for bone defect treatment, graphene oxide (GO) in particular has gained substantial attention from researchers due to its potential applications and prospects. In other words, GO scaffolds have demonstrated remarkable potential for bone defect treatment. Furthermore, GO-loaded biomaterials can promote osteoblast adhesion, proliferation, and differentiation while stimulating bone matrix deposition and formation. Given their favourable biocompatibility and osteoinductive capabilities, these materials offer a novel therapeutic avenue for bone tissue regeneration and repair. This comprehensive review systematically outlines GO scaffolds’ diverse roles and potential applications in bone defect treatment. Cite this article: Bone Joint Res 2024;13(12):725–740.